COMPOSITIONS AND METHODS FOR APPLICATION OVER SKIN - AKTHAKUL, Ariya (2020)
Disclosed herein are compositions that can be used to create a thin film on the skin of a subject in a single application step to the skin of the subject. More specifically, a composition provided herein does not have to be stored in multiple compartments, nor mixed with another composition or component before application to the skin. Instead, a single composition can be manufactured, stored in a single compartment, and then applied to the skin of a subject to create a film on the skin of the subject. In certain embodiments, because there is no need to mix a composition provided herein prior to application to the skin, the container comprising a composition provided herein may also include an applicator suitable for application of the composition to the skin. L'invention concerne des compositions qui peuvent être utilisées pour créer un film mince sur la peau d'un sujet en une seule étape d'application sur la peau du sujet. Plus précisément, l'invention concerne une composition qui n'a pas à être stockée dans de multiples compartiments, ou mélangée avec une autre composition ou composant avant application sur la peau. Au lieu de cela, une composition unique peut être fabriquée, stockée dans un seul compartiment, puis appliquée sur la peau d'un sujet pour créer un film sur la peau du sujet. Dans certains modes de réalisation, étant donné qu'une composition de l'invention n'a pas à être mélangée avant application sur la peau, le récipient qui contient la composition peut également comprendre un applicateur approprié pour appliquer la composition sur la peau.